2016
DOI: 10.1007/s00784-016-1925-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of the utilization of vital Lugol’s iodine staining in detection and diagnosis of oral cancer and dysplasia

Abstract: Lugol's iodine staining can effectively be used in detection of the dysplastic and malignant superficial lesions of the oral epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Lugol iodine staining test is currently used for intraoperative assessment of head and neck cancer in the attempt to diagnose the disease as early as possible, and provide the best therapeutic option for every patient [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…Lugol iodine staining test is currently used for intraoperative assessment of head and neck cancer in the attempt to diagnose the disease as early as possible, and provide the best therapeutic option for every patient [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…In the literature different authors have used different concentrations of lugol iodine solution. The most frequent concentrations found are 1%; 3% and 10% [16,20,21], but other concentrations were reported as well: 1.5, 2, 5% [22][23][24][25]. We are using 3% lugol iodine solution with good results in staining the oral cavity tissue structures.…”
Section: Resultsmentioning
confidence: 99%
“…In OSCC, CIS, and low- and high-grade OED, little glycogen is present in the granule cell layer, resulting in iodine unstained (IU) areas [ 12 , 27 ]. However, IS cannot be used for patients with iodine allergy, and the technique is invasive [ 28 ]. IS is applicable for movable mucosae such as the tongue, oral floor, buccal mucosa, and soft palate, but is difficult to use on keratinized mucosa such as the gingiva and hard palate [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…IS is applicable for movable mucosae such as the tongue, oral floor, buccal mucosa, and soft palate, but is difficult to use on keratinized mucosa such as the gingiva and hard palate [ 10 ]. It was reported that 53.1% and 21.4% of patients feel discomfort and pain, respectively, with IS [ 28 ]. According to reports [ 12 , 27 , 28 , 29 ], the sensitivity and specificity for detection oral cancer are 56.0% and 46.8% [ 29 ], and 88.5 and 51.6% [ 12 ].…”
Section: Discussionmentioning
confidence: 99%